1996
DOI: 10.1164/ajrccm.153.6.8665054
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and cross-sectional analyses of lung function in steelworkers.

Abstract: We evaluated associations between dust exposure, demographic factors, and lung function by longitudinal and cross-sectional analyses in 475 steelworkers who participated in at least three spirometry tests over 5 yr between 1982 and 1991. Baseline and follow-up spirometry and changes between baseline and final follow-up assessment attributable to age, height, weight, weight gain, smoking status, pack-years, and years worked in dusty areas were examined using stepwise multiple linear regression techniques. Smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 12 publications
7
28
1
Order By: Relevance
“…There are a large number of reports on the effect of smoking in reducing pulmonary function in pneumoconiosis 22,25,29,[31][32][33][34][35][36][37] . In this study, smoking habit was not analyzed, since a survey on smoking was not included in the pneumoconiosis health examination.…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of reports on the effect of smoking in reducing pulmonary function in pneumoconiosis 22,25,29,[31][32][33][34][35][36][37] . In this study, smoking habit was not analyzed, since a survey on smoking was not included in the pneumoconiosis health examination.…”
Section: Discussionmentioning
confidence: 99%
“…The present longitudinal study selected smoking as a predictor of VC and FEV 1 , which decreased 6.1 and 5.8 ml/y, respectively. Several previous longitudinal studies reported that smoking was strongly related to a decline in lung functions not only in subjects with pneumoconiosis 7,15,17,18,22,24,25) , but also in a healthy population 32) . The study by Soutar and Hurley 18) of British coal miners reported that according to the statistical model at age 60 and zero dust exposure, mean FEV 1 in ex-smokers and current smokers was 212 ml and 327 ml lower than that of never-smokers, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…However, many of the Japanese studies were cross-sectional [2][3][4][5] and only a small number were longitudinal [6][7][8] . In other countries, several longitudinal studies focused on individual occupational categories [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] although studies across categories through a study area were rare 28) . The present study focused on workers exposed to one or more of 17 types of dust categories listed in the Enforcement Ordinance of Pneumoconiosis Law 29) .…”
Section: Introductionmentioning
confidence: 99%
“…However, Pham et al detected a significant deterioration of FEV 1.0 and FEV 1.0 %FVC in steelworkers compared with a reference group of unexposed workers in a five-year longitudinal study 2) . Wang et al found significant loss of FEV 1.0 , FVC, and FEV 1.0 %FVC at the cross-sectional baseline data, whereas the association between dust exposure and longitudinal decline of lung function was weak 4) . Nemery et al also showed that the more pronounced decrease in FEV 1.0 and FEV 1.0 %FVC found over the night shift of strandcasting workers in an over 21 d shiftwork 3) .…”
Section: P-c Chen Et Almentioning
confidence: 97%
“…Hazardous dust is one of the most important exposures in steelworkers. There are only a few published studies on the respiratory health of steelworkers and these have showed that chronic bronchitis and decreased lung function values [1][2][3][4][5] are associated with atmospheric pollution, especially in the coke oven plant [6][7][8][9] . However, all of them lacked an appropriate assessment of dust exposure, especially the respirable fraction, leaving the question of association between actual amount and respiratory impairment still unanswered.…”
Section: Introductionmentioning
confidence: 99%